Microbial Biofilms 2015
DOI: 10.1128/9781555817466.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Candida Biofilms: Development, Architecture, and Resistance

Abstract: Intravascular device-related infections are often associated with biofilms (microbial communities encased within a polysaccharide-rich extracellular matrix) formed by pathogens on the surfaces of these devices. Candida species are the most common fungi isolated from catheter-, denture-, and voice prosthesis-associated infections and also are commonly isolated from contact lens-related infections (e.g., fungal keratitis). These biofilms exhibit decreased susceptibility to most antimicrobial agents, which contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 153 publications
1
16
0
1
Order By: Relevance
“…are an increasingly recognised clinical problem and most antifungal agents show limited penetration into and thus activity against biofilms. 65,75,76 The main exception is the echinocandin class, which shows superior activity against biofilms compared to other antifungals. 65 The most important measure for successful treatment of biofilm infections remains, however, removal or exchange of the vascular device or foreign body containing the biofilm.…”
Section: Iatrogenic Factorsmentioning
confidence: 99%
“…are an increasingly recognised clinical problem and most antifungal agents show limited penetration into and thus activity against biofilms. 65,75,76 The main exception is the echinocandin class, which shows superior activity against biofilms compared to other antifungals. 65 The most important measure for successful treatment of biofilm infections remains, however, removal or exchange of the vascular device or foreign body containing the biofilm.…”
Section: Iatrogenic Factorsmentioning
confidence: 99%
“…From our experience, we propose injections in an interval of 2-3 days. Another important step is repeated corneal debridement, as the debridement of necrotic material and the removal of the fungal biofilm allows better penetration of topical treatments [19]. Lalitha et al [20] have showed that an ulcer area of more than 14 mm 2 , or the presence of a hypopyon and infection with Fusarium spp are risk factors for treatment failure.…”
mentioning
confidence: 99%
“…W przypadku opisanej wyżej chorej, wobec wczesnego okresu po transplantacji od dawcy niespokrewnionego, interwencja chirurgiczna obarczona była szczególnie wysokim ryzykiem powikłań. Biorąc pod uwagę zdolność grzybów Candida do tworzenia biofilmu na powierzchni wsierdzia zastawek zarówno natywnych jak i sztucznych, który istotnie utrudnia możliwość penetracji leku do miejsca zakażenia i tym samym pełną aktywność terapii, stosowanie leczenia przeciwgrzybiczego z użyciem dwóch leków o innym mechanizmie działania może być bardziej efektywne [20]. Połączenie liposomalnej amfoterycyny B z lekiem z grupy echinkandyn daje szansę na zwiększenie skuteczności leczenia bez nasilenie efektów toksycznych [21].…”
Section: Omówienieunclassified